Unilateral Sympathectomy for Primary Palmar Hyperhidrosis - Ravari, Hassan; Rajabnejad, Ataollah (The Thoracic and Cardiovascular Surgeon, 2015)
Background and Objective Primary palmar hyperhidrosis that arises mostly during puberty and early adolescence has a tremendous impact on the quality of life in patients. This study aimed to investigate the effectiveness of unilateral video-assisted thoracic sympathectomy for dominant hand in these patients.Patients and Methods From July 2010 to June 2013, 52 patients with primary palmar hyperhidrosis underwent unilateral video-assisted thoracoscopic sympathectomy for dominant hand. We analyzed the outcomes regarding the resolution of symptoms, occurrence of complications, recurrence rate, and compensatory hyperhidrosis, and need of operation for opposite side.Findings All patients were followed up from 6 to 42 months. Palmar hyperhidrosis was completely alleviated and absolute dryness was achieved in all patients at the same hand after the operation. Palmar hyperhidrosis in the opposite hand was cured to a complete dryness in 24 (46.15%) patients. No change happened in the opposite hand in 22 (42.3%) patients, but an increase was seen in 6 (11.53%) patients. Only seven (13.46%) patients needed to undergo contralateral sympathectomy. Compensatory hyperhidrosis occurred in 13 patients (25%) after unilateral sympathectomy. Another five patients (totally 18, 34.6%) were involved with compensatory hyperhidrosis after contralateral sympathectomy. It was mainly on the trunk in all 18 patients.Conclusion Unilateral dominant side thoracoscopic sympathectomy for patients with primary palmar hyperhidrosis is an effective, safe, and minimally invasive procedure. Only a small number of patients will eventually require a contralateral sympathectomy in nondominant hand.
Keywords: primary hyperhidrosis; sympathectomy; unilateral; palmar hyperhidrosis